REPRESENTASI BENCANA DALAM FOTO SERI “CERITA KLOSET PASCAGEMPA-TSUNAMI PALU” (STUDI ANALISIS SEMIOTIK TERHADAP FOTO SERI KARYA BEAWIHARTA YANG DIMUAT DI BERITASATU.COM) - Dian Aprilianingrum (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Disaster representation of series photo “Toilet stories after earthquake –tsunami Palu (Analysis Study On series photo by Beawiharta)  analyzed by using Barthes semiotics that was about denotation, connotation and myth. Data sources were primary data sources (photographs) and secondary data sources (literature that supports primary data such as dictionaries, internet, thesis, books). The method used in this study is a qualitative research method that is descriptive analysis, i.e. research that provides an objective picture, with Barthes analysis of photo series.  This study chose 1 representative photo from 10 photos at the series. The photo showed toilet among debris at Mamboro and Talisse Beach, Palu, Central Sulawesi. The conclusion of the research showed that 1. Photo visualized aftermath by showing contrast between toilet and debris. 2. Photo visualized massive destruction that force citizen to rebuild their life. 3. There is myth cause of earthquake and tsunami.